Relationship Of Age, Gender, Location Insertion And Catheter Size Of Incidence Phlebitis - Paul Joae Brett Nito; Setiawati Setiawati; Murtiningsih Murtiningsih (Universitas Sari Mulia, 2018)
Background: Children is a hope of future that must be protected and cared for as well as possible. Children are at risk of having health problems, one of them phlebitis. Phlebitis is an inflammation or irritation of the vein walls caused by mechanical, chemical, bacterial or internal factors. Phlebitis incidence in Indonesia in 2013 is about 50,11% for Government Hospital and 32,70% Private Hospital.Objective: This study aims to determine the relationship of age, gender, location insertion and catheter size that cause phlebitis in the ward of children Ulin Hospital Banjarmasin.Methods: An observational analytic study with a cohort approach. Sampling technique used is consecutive sampling. Data were collected using respondent's observation sheet and Visual Infusion Phlebitis Scale (VIP Scale). Data analysis using chi-square test. The sample of this study were children who received intravenous therapy with 80 children.Results: The results showed that age, sex, location insertion and catheter size no significant relationship with phlebitis incidence (p 0.05).Conclusion: These findings suggest that nurses have to improve the ability to determining the risk of phlebitis occurrence in patients.Â Keyword: children, risk factors, phlebitis, Visual Infusion Phlebitis Scale